2004
DOI: 10.1046/j.1397-3142.2003.00115.x
|View full text |Cite
|
Sign up to set email alerts
|

The yield of surveillance endomyocardial biopsies as a screen for cellular rejection in pediatric heart transplant patients

Abstract: Endomyocardial biopsy is commonly used to screen for cellular rejection in pediatric heart transplant patients. The yield of EMBs when combined with newly developed immunohistochemical techniques and modern immunosuppression in pediatric heart transplant patients is unknown. After OHT, surveillance biopsies were performed on a routine basis on all pediatric patients. EMBs were also performed on symptomatic OHT patients suspected to have rejection. All positive results (greater than ISHLT grade 1B) were confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 19 publications
0
40
1
2
Order By: Relevance
“…Alternatively, many institutions employ tacrolimus, which may reduce the need for surveillance endomyocardial biopsies because of fewer rejection episodes. 20 Although the latter agent costs more, it has been suggested that the additional costs may be offset by fewer rejection episodes-although this argument is controversial. 21 Benchmarks are used to compare the cost-effectiveness of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, many institutions employ tacrolimus, which may reduce the need for surveillance endomyocardial biopsies because of fewer rejection episodes. 20 Although the latter agent costs more, it has been suggested that the additional costs may be offset by fewer rejection episodes-although this argument is controversial. 21 Benchmarks are used to compare the cost-effectiveness of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…2 Despite this failure rate, the incidence of cellular rejection on endomyocardial biopsy (EMB) has been reported at only 0% to 8% for asymptomatic patients and 9% to 41% for symptomatic patients. 3,4 Furthermore, there is often no mention of humoral rejection (HR) in the literature on rejection episodes and development of transplant coronary artery disease (TCAD). 5,6 Data from the adult heart transplant literature suggest that HR is a significant cause of biopsy-negative, hemodynamically significant rejection episodes and graft failure.…”
mentioning
confidence: 99%
“…Levi et al showed only a 0.36% incidence of EMB-positive rejection (ISHLT Grade ≥1B) in asymptomatic patients on tacrolimus therapy (770 biopsies) during the first year after transplant, and no asymptomatic patient had a positive biopsy at >1 year after transplant. 10 In contrast, other reports suggest RSB continues to detect late episodes of MSR. Kuhn et al reported an 8% to 10% annual incidence of moderate rejection up to 11 years after transplantation in a study including 269 children with a mean follow-up time of 5 years.…”
Section: Discussionmentioning
confidence: 91%
“…Previous single-center studies have shown a decreased incidence of positive surveillance biopsies (at least during the first year) in patients treated with tacrolimus compared with cyclosporine. 8,10 This study contained the expected limitations that accompany a retrospective database study. A significant amount of potential data were excluded due to lack of the main study variable.…”
Section: Discussionmentioning
confidence: 99%